The Application of the Forward-Backward Chaining Method in Analyzing Oil Palm Plant Diseases at PT. Fajar Agung - Intan Salwa Salsabila (Al'adzkiya International of Computer Science and Information Technology (AIoCSIT) Journal, 2024)
Bengabing Plantation is a pure plantation managed by a national private company, PT. Fajar Agung, which operates in the oil palm and rubber plantation sector. A frequent decline in harvest yields has been observed, caused by pests and diseases affecting the oil palm plants. Therefore, a medium is needed to help address this issue—namely, an expert system for diagnosing oil palm diseases. The aim of this research is to develop an expert system that can replicate the knowledge of plantation experts, particularly in the field of oil palm cultivation, into a computerized system by applying the forward-backward chaining method.